EFFECT OF CUTTING LENGTH IN ROOTING OF TEA TREE - OLIVEIRA, Yohana de; SILVA, André Luís Lopes da; PINTO, Fernanda; QUOIRIN, Marguerite; BIASI, Luiz Antonio (Scientia Agraria, 2008)
Melaleuca alternifolia Cheel (Myrtaceae), also known as "tea tree", is a native tree of Australia with great economic importance due to extraction of essential oils from its leaves. This oil is used in the pharmaceutical industry for its antimicrobial and antifungical action. The main problem for the expansion of the culture of Melaleuca alternifolia is the production of plants and studies on the vegetative propagation of this species are scarce. The objective of this study was to evaluate the influence of three lengths of cutting on the adventitious rooting. Apical cuttings were prepared with 10, 15 and 20 cm of length (measured from the apex to the base), cut in bevel at the base. One third of the leaves was kept in the apical portion and the cuttings were treated with 1500 mg L-1 IBA. For the plantation under greenhouse, tubes of polypropylene with capacity of 53 cm3 and containing Plantmax HT® substrate were used. The cuttings were kept in greenhouse under mist. After 120 days, the percentage of adventitious rooting and survival, the average number of roots per cutting and the average length of the three main roots per cutting were evaluated. In conclusion, 10 cm cuttings of M. alternifolia show higher rooting percentage than 15 or 20 cm cuttings.